“No peace…I have no peace” : continuous traumatic stress and resilience in Asylum seekers living in Johannesburg - Singh, Letisha (My University, 2017)
The study sought to describe the experiential and symptomatic dimensions of ongoing traumatic stress in asylum seekers living in South Africa and explore the ways in which they managed in a context in which they were exposed to potential violence and severe stressors. Six asylum seekers were interviewed on their experiences of past trauma, the emotional and psychological impact of exposure to ongoing stress in the absence of protections in South Africa and the resources they drew upon in order to manage in such climates. The study used a qualitative design and a general descriptive exploratory approach in order to capture these experiences. Individual interviews were conducted with participants and a thematic content analysis technique was used to analyse the resulting transcripts. Findings revealed that CTS as a construct had some utility in being able to conceptualise the socio-political nature of the ongoing trauma oppressed population groups such as asylum seekers were exposed to. While the study was able to locate past as well as current stressors which contributed to ongoing traumatic stress in the form of pre-migration experiences and post-migration stressors respectively, the CTS construct was unable to fully account for the emotional and psychological impact of having to engage with stresses associated with post-migration experiences (oppression, subjugation, and marginalization), in non-facilitative contexts such as participants had found Johannesburg to be. The symptom presentation of asylum seekers appeared to not only include trauma related reactions but also further responses, including depressive and somatic sequelea, related to having to re/engage with historical and current stresses and the lack of protections associated with these. Findings suggest that if ongoing traumatic stress is to be conceptualised in certain oppressed population groups a more circular model is required which considers the inter-related impact of stressors in the past (pre-migration traumatic exposure) with stressors in the current context (which may or may not be strictly traumatic, but which heighten threat anxiety) and in which lack of social 6 protections gives rise to the anticipation of future maltreatment based on one’s identity/position in society. The study considered the various coping strategies which asylum seekers drew on to manage in the post-migration context. It was found that marginalization forced asylum seekers into an insular position in society in which primary reliance was on themselves and intrapersonal dimensions of resilience, with only some value being gained from community related forms of support. This ‘coping picture’ appeared to limit asylum seekers’ social capital building capacity which appeared to place the population at greater risk of developing “ongoing traumatic responses”.
A dissertation submitted in partial fulfilment of requirements for the degree of Master of Arts At the University of Witwatersrand, Johannesburg 2017